Evaluating alternative approaches for predicting pension benefits and incentives. (18th October 2021) - Knapp, David; Lis, Maciej; Lee, Jinkook; Phillips, Drystan
Abstract: In an effort to promote comparative research on pensions, the Gateway to Global Aging Data is developing harmonized cross-national panel data on pension benefits and retirement incentives. Past research has varied in how it predicts pension benefits for individuals who have not yet claimed their benefits when administrative data on earnings histories is unavailable. We use the Gateway data to evaluate several alternative approaches to computing prospective pension benefits using common survey questions and validate them against matched administrative data. We find that in some settings naïve measures of pension benefit growth from continued work and delayed benefit claiming can perform as well as measures based on administrative data. We also find that prospective benefit levels are sensitive to the heterogeneity of lifecycle earnings dynamics, resulting in substantial measurement error even after accounting for work history.